1994
DOI: 10.1111/j.1528-1157.1994.tb02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Global Aphasia with Seizure Onset in the Dominant Basal Temporal Region

Abstract: A 33-year-old right-handed woman had intractable simple and complex partial seizures (SPS, CPS) that began with global aphasia. EEG closed-circuit TV (EEG-CCTV) monitoring with sphenoidal electrodes showed left inferomesial temporal ictal onset of CPS. Subdural electrodes were implanted over the left frontotemporal convexity, subtemporally and subfrontally. Stimulation of the basotemporal cortex produced global aphasia. A posterolaterotemporal language area was also identified. Spontaneous SPS had focal onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Language disturbance associated with electrical stimulation of the BTLA ranges from isolated anomia to global aphasia 14 . Abou-Khalil et al also reported a patient with global aphasia resulting from a seizure focus in the left basal temporal region 16 . An alternative account for the global aphasia might be that the patient had temporal lobe seizures resulting in postictal dysphasia due to the spread of the ictal and postictal dysfunction into the language centers in the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Language disturbance associated with electrical stimulation of the BTLA ranges from isolated anomia to global aphasia 14 . Abou-Khalil et al also reported a patient with global aphasia resulting from a seizure focus in the left basal temporal region 16 . An alternative account for the global aphasia might be that the patient had temporal lobe seizures resulting in postictal dysphasia due to the spread of the ictal and postictal dysfunction into the language centers in the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, speech areas are located in the dominant frontal and temporal lobe . Not surprisingly, SAA has been reported in frontal and temporal epilepsies (Table ) . However, these studies included mostly patients with temporal and frontal epilepsies.…”
Section: Summary Of Previously Reported Patients With Saamentioning
confidence: 99%